PENGENALAN NILAI-NILAI AKHLAK MULIA MELALUI METODE PEMBIASAAN DI RA AL ROSYID BOJONEGORO - Ulfa Mansyur (AL-AUFA: JURNAL PENDIDIKAN DAN KAJIAN KEISLAMAN, 2020)
Education is a lifelong human need, early childhood education aims to provide stimulation and guidance on physical tenderness and growth, so as to improve intellectual abilities and social relations in preparation for further education. Children are parents' hopes, their education must be considered since they are at an early age, because at an early age giving education to them is very influential. Today's many community phenomena cannot be controlled in their moral values, because of lack of good education at an early age, and in providing education at an early age must be a method that is easy for them to understand, then the introduction of moral values should be given since the child early age and with the correct method among the methods is the habitual method. to see this truth the author took research at the RA al Rosyid Bojonegoro school, which became a favorite school in that city